Teneurs Des Éléments Traces Métalliques Cu, Zn Et Pb Des Sédiments Du Barrage Béni Haroun (Nord-Est De l’Algérie) - Hamssa Djeddi; Saliha Kherief Nacereddine; Dounia Keddari; Fatima-Zohra Afri-Mehennaoui (European Scientific Journal, ESJ, 2018)
This paper focuses on evaluating the degree of three metal pollution (Cu, Zn and Pb) in the sediments of Béni Haroun dam, located in northeastern of Algeria. For this reason, the superficial sediments were sampled at five stations, and the samples were taken at different seasons of the year. The results show low Cu and Zn levels which reflect natural conditions in relation to the area of geological nature. It also highlights the presence of Pb contamination (2.29 to 91.86µg/g). This result was also confirmed by various indices, including the geoaccumulation index (Igeo) and the contamination factor (FC). The Igeo values for Pb show moderate contamination of the Bge2 and Bge3 stations. CF values indicate moderate to considerable contamination for most stations by Pb. However, low or absent of Zn contamination was noted in all stations except for the Bge5. The correlation matrix and the PCA between all metal elements indicates that they were derived from similar sources. The contamination sources would probably establish a significant relationship between runoff and the erosion of agricultural lands. It is therefore an anthropogenic metal pollution related to agricultural activity using fertilizers and pesticides.